Економічний аспект впливу вихрових струмів на електричний опір струмопровідних жил високовольтних кабелів із зшитою поліетиленовою ізоляцією - Голик, Оксана Вячеславівна (НТУ "ХПІ", 2011)
Наведені основні економічні аспекти впливу вихрових струмів на електричний опір струмопровідних жил високовольтних кабелів із зшитою поліетиленовою ізоляцією.

The basic economic aspects of vortical currents influence on the electric resistance in high-voltage cable currents with the sewed polyethylene isolationfluence are resulted.
Economic aspect of vortical currents influence on electric resistance in high-voltage cable currents with the sewed polyethylene isolation
Keywords: площа поперечного перерізу; коефіцієнт заповнення жили; міжнародні стандарти; конструкція; high-voltage cable; cable currents; vortical currents; electric resistance; determination; economic aspect